(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Githa Hariharan is among the most important Indian English females’ writers that have been producing a body of Indian literature that’s devoted to social problems as well as feminist. The very first novel of her, ‘The 1000 Faces of Night’ (1992) won the Common Wealth Writers Prize for Best First Book in 1993. Githa Hariharan in the novel of her Fugitive Histories reflects the plight of Muslim females’ victims of the Godhra riots as well as the aftermath of its. The practical account paralleled with the fiction is actually Gujarat pogrom of 2002. The tropes of the past, the worrisome present as well as the ambiguous future of the marginalized is actually questioned in the fiction.